Can India Achieve Double-digit growth ? - Herd, Richard (OECD Publishing, 2011)
In recent years, India has enjoyed one of the highest growth rates worldwide, weathering the global financial crisis better than many other countries. Prudent macroeconomic policies will be critical to prolonging the current expansion, given the risks associated with high inflation and volatile capital flows. A steadfast commitment to fiscal consolidation is needed to continue to reduce the large deficit that emerged in the aftermath of the slowdown and avoid crowding out private investment. Stepping up structural reforms will also be necessary if double-digit growth rates are to be achievable over the coming decade or so. Indeed, the operating environment for private business remains challenging. While infrastructure is improving in key sectors, partly thanks to greater private investment, bottlenecks endure and efforts to intensify competition and ensure continued strong investment are required. Labour market reforms are also required to promote job creation. Rapid economic development has boosted living standards and reduced poverty but poverty remains high. There is a need to strengthen social welfare systems and access to health and education to ensure widespread benefits from continued high growth. This Working Paper relates to the 2011 OECD Economic Survey of India (www.oecd.org/eco/surveys/india)
Keywords: Economics; India